2005
DOI: 10.1017/s0950268805004127
|View full text |Cite
|
Sign up to set email alerts
|

A multi-state outbreak of Salmonella serotype Thompson infection from commercially distributed bread contaminated by an ill food handler

Abstract: Foodborne transmission is estimated to account for 95% of non-typhoidal Salmonella infections reported in the United States; however, outbreaks of salmonellosis are rarely traced to food handlers. In August 2000, an increase in Salmonella serotype Thompson infection was noted in Southern California; most of the cases reported eating at a restaurant chain (Chain A) before illness onset. A case-control study implicated the consumption of burgers at Chain A restaurants. The earliest onset of illness was in a burg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 14 publications
1
32
0
3
Order By: Relevance
“…The level of resistance of Salmonellae to antibiotics should be alarming to the food processing, distribution and handling of food product [18,19]. Therefore, it is necessary to inform people involved in the food industry as well as distributors to take care in handling the food products.…”
Section: Resultsmentioning
confidence: 99%
“…The level of resistance of Salmonellae to antibiotics should be alarming to the food processing, distribution and handling of food product [18,19]. Therefore, it is necessary to inform people involved in the food industry as well as distributors to take care in handling the food products.…”
Section: Resultsmentioning
confidence: 99%
“…Details of outbreaks associated with S. Thompson have been published previously (1)(2)(3)(4). One outbreak which occurred in 2012 involved 1,149 confirmed cases in the Netherlands, which was attributed to the consumption of smoked salmon (1).…”
Section: Introductionmentioning
confidence: 99%
“…One outbreak which occurred in 2012 involved 1,149 confirmed cases in the Netherlands, which was attributed to the consumption of smoked salmon (1). Other studies have identified various vehicles: bread, possibly contaminated by a food handler (2); fresh cilantro (3); and rucola grown in Italy (4). In Canada, two national outbreaks have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of Salmonella enterocolitis are food-borne. Contaminated eggs and poultry are common sources of infection, but outbreaks have also been triggered by meat, fruit, nuts and even bread (4,5). Approximately 15% of cases involve other routes of transmission, including contaminated water, direct person-to-person contact, and laboratory-acquired infections.…”
mentioning
confidence: 99%